Status of Glucose-6 Phosphate Dehydrogenase Enzyme in Patients with Hemolytic Anemia - Razzak, M; Begum, N; Hossain, MD (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Glucose-6 Phosphate Dehydrogenase (G-6PD) enzyme deficiency is an important cause of hemolytic anemia. Acute hemolytic crisis may occur in G-6PD enzyme deficiency due to some oxidative stress. Hemolysis of RBC may occur even without prior administration of drugs in patients with G-6PD enzyme deficiency. Erythrocyte and serum level of G-6PD enzyme are lower in most of the patients with hemolytic anemia Objectives: To assess the status of erythrocyte and serum level of G-6PD enzyme in patients with hemolytic anemia. Method: The cross sectional study was carried out in the Department of physiology, BSMMU, Dhaka from July 2002 to 2003 to observe the status of Glucose-6 Phosphate Dehydrogenase (G-6PD) enzyme in patient with hemolytic anemia. For this, total number of 50 hemolytic anemic patients (Groups-B) with age ranged from 5 to 30 years of both sexes was studied. Among them, 25 were without G-6PD deficient hemolytic anemia (group-B1) and 25 were hemolytic anemia with G-6PD deficiency(group-B2).Age and sex matched 30 apparently healthy subjects with normal blood G-6PD were included to observe baseline data (Group-A) and also for comparison. The subject was selected from out Patient Department of Hematology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Blood erythrocyte and serum levels of G-6PD enzyme level were measured by standard laboratory techniques. Analysis of data was done by unpaired student 't' test. Results: Both erythrocyte and serum level of G-6PD enzyme levels were significantly lower in patients with hemolytic anemia. Conclusion: Erythrocyte and serum level of G-6PD enzyme may play important role in the diagnosis of hemolytic anemia with or without G-6PD enzyme deficiency and may help in prompt patient management. J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 17-20